Double-Blind Acupuncture Needle: A Potential Tool to Investigate the Nature of Pain and Pleasure - Takakura, Nobuari (Hindawi Publishing Corporation, 2013)
Background. Most of our knowledge about similarities in the neural processing of painful and pleasant sensations in the brain derives from studying each phenomenon separately. Patients often feel pain induced by acupuncture, which is noxious stimulation having the symbolic message of the cure, as pleasant. Objectives. We investigated whether the double-blind acupuncture needles are a potential tool to investigate coinciding pain and pleasant events. Methods. Participants were 109 healthy acupuncture students. An acupuncturist applied the double-blind placebo and the matching penetrating needle at bilateral forearm of each subject, one needle on each side of the arm. We asked the subjects to rate the pain associated with needle application and its unpleasantness or pleasantness on a visual analogue scale. Results. Of 65 penetrating needle applications that elicited pain, 29 (45%) subjects did not describe the pain as being unpleasant, and interestingly, 18 (28%) subjects described the needle insertion as pleasant. There was no significant difference in reported pain intensity between penetrating needles elicited pain that elicited a pleasant sensation and those that elicited an unpleasant sensation (P = 0.34). Conclusions. The double-blind acupuncture needles can be a potential tool for investigating the concomitant hedonic (pleasure) experience of pain.